The Emergence of Communicative Language Teaching in the English Language Learning and Teaching Context - Lalu Azizan Bohari (Jurnal Ilmiah Profesi Pendidikan, 2026)
English has gained a prominent role in today's globalisation-functioning as an international language-conveying communicative messages as well as connecting people from diverse cultural and linguistic backgrounds. Being able to speak the language fluently and appropriately enables the speakers to interact more effectively. The majority of English learners, however, still have difficulty coping with the target language in spite of being instructed for years. One of the most salient problems facing the learners is the use of the irrelevant and monotonous approaches to language learning and teaching. For this reason, this article attempted to explicate the notion of Communicative Language Teaching, the so-called CLT, which is viewed as a contemporary and complementary approach to the previous ones, focusing on the optimal attainment of the communicative competence and to delve into numerous attributes contributing to its emergence in the English Language Learning and Teaching (ELT) context by highlighting the theoretical concepts underlying such approach. Synthesizing the relevant sources of the conceptual data, the CLT emphasised several significances for the learners: being communicatively skilful; mastering vocabulary and grammar; and understanding the function over form of language. It finally proposed the implications for the teaching practitioners to take into consideration in their attempts to succeed in the classroom teaching endeavours.